Evolution of physical performance in professional soccer across four consecutive seasons - Radziminski, L.; Jastrzebski, Z. (Baltic Journal of Health and Physical Activity, 2021)
Background: Main purpose of this research was to investigate the changes of physical match performance in Polish Ekstraklasa across four consecutive seasons. Material and methods: A total of 949 official matches from season 2017/2018 to 2020/2021 were analyzed. Such match running performance variables as total distance, high-speed running, sprinting, and number of high-intensity runs were involved. Each season data were divided into two rounds (spring round and autumn round). Due to the pandemic of COVID-19 additional post-lockdown round (Spring I 2019/2020) occurred. Results: Comparison in the results between Spring 2017/2018 and Spring 2020/2021 indicated significant increases in total distance (2.1%, p<0.001), high-speed running (11.9%, p<0.001), sprinting distance (7.7%, p<0.01) and number of high-intensity runs (9.7%, p<0.001). Moreover, within season analysis exhibited that during spring rounds Ekstraklasa teams covered significantly longer (p<0.01) distances in high-speed running than during autumn rounds. Reduction in physical match performance was reported after the 12-week pandemic lockdown. Conclusions: The results of this study confirmed the growing importance of such match activities as high-speed running, sprinting and number of high intensity runs which increased in Polish Ekstraklasa by 8-12% within last 4 years. This growing tendency was disrupted by unexpected off-season period caused by COVID-19 lockdown.